PRAKSIS DEMOKRASI PENDIDIKAN DALAM KURIKULUM MERDEKA DAN RELEVANSINYA BAGI PENGEMBANGAN PENDIDIKAN KARAKTER - Siswadi, Gede Agus (Widya Aksara : Jurnal Agama Hindu, 2025)
Education is a fundamental principle in shaping the character of children. Thus, education becomes important in internalizing character values ​​that must be contained in curriculum design. Because basically, the curriculum is a reference to determine the direction of education. Therefore, this study aims to explore the newest curriculum, namely the Merdeka Curriculum. In addition, this research is also intended to find the philosophical basis in the Merdeka Curriculum, educational praxis in the Merdeka Curriculum, and how the relevance of the Merdeka Curriculum is in the development of character education. This study uses a qualitative method with a descriptive approach. The results of this study indicate that the philosophical basis of the Merdeka Curriculum, namely ontologically the Merdeka Curriculum essentially gives freedom and independence to students to learn. The Merdeka Curriculum focuses more on optimizing for the growth of all the potential possessed by students. The epistemological foundation in the Merdeka Curriculum is the exploratory method to gain contextual knowledge. The axiological foundation in the Merdeka Curriculum is more oriented toward personal development and also the skills of students. The praxis of education in the Merdeka Curriculum shows the praxis of educational democracy. the development of character education in the Merdeka Curriculum is manifested in student profiles and there are six dimensions that must be emphasized in strengthening Pancasila student profiles, namely: 1) faith, fear of God Almighty, and having noble character, 2) independence, 3) mutual cooperation, 4) global diversity, 5) critical reasoning, and 6) creative.